Protocol for evidence synthesis of market intelligence: Application to rice in the global South - Custodio, Marie Claire; De Steur, Hans; Demont, Matty (CGIAR, 2023)
Demand-oriented crop breeding relies on market intelligence to support market segmentation, target product profile (TPP) design, alignment of breeding pipelines, and prioritization and allocation of investments. Synthesis of existing evidence such as stakeholder preferences (e.g., consumers, farmers) is needed to inform discussions on the expectations and requirements of actors along rice value chains and the implications for current and future rice markets segments and product design. We designed a protocol carrying out a systematic literature review (SLR) as a tool for evidence synthesis. We used this protocol to review and synthesize current stakeholder requirements for rice seed products in the global South. The protocol can be used by researchers to synthesize market intelligence for specific market segments and/or other crops. At the global level, our findings suggest that the traits preferred by stakeholders are generally considered in the current portfolio of rice market segments and TPPs. This analysis can be scaled down to the market-segment level to verify whether the traits proposed in the TPPs are in line with stakeholder requirements in each market segment. Broadly, maturity, texture, and grain color are considered important in the reviewed farmer and consumer studies, and these are among the basic criteria for market segmentation. Specifically, farmer requirements for agronomic traits focus on yield, maturity, plant height, lodging tolerance, and tillering ability. These are generally included as essential traits in the rice TPPs. Through the systematic approach, potential areas for future research have been identified. In terms of geographical regions, we found that peer-reviewed publications on farmer evaluation of seed products and consumer preferences for rice are underrepresented in South Asia and in Africa. In terms of value chain stakeholders, we found limited evaluation by midstream stakeholders (i.e., processors). In terms of attributes, evidence on evaluation of chalkiness was missing in the reviewed studies. Limited evaluation of nutrition-related attributes was also found, which suggests that more research to identify future market segments for nutrition attributes.